Pengaruh Dewan Komisaris, Firm Size, dan Rasio Modal terhadap Profitabilitas Asuransi Jiwa Syariah di Indonesia - Uyun, Syifaul; Nasution, Zubaidah; Setiawan, Surya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to analyze the effect of the Board of Commissioners, Firm Size, and Capital Ratio on the Profitability of Sharia Life Insurance in Indonesia for the 2016-2021 period. The method of determining the sample in this study was purposive sampling method and the results obtained were 10 sharia life insurance companies in Indonesia. The data analysis in this study is descriptive analysis and multiple linear regression analysis using SPSS 17. This research results that simultaneously the board of commissioners, firm size, and capital ratios have a significant effect on profitability. While partially the board of commissioners has no significant effect, firm size and capital ratios have a significant effect on profitability. Keywords: Board of Commissioners, Firm Size, Capital Ratio, Profitability